The Impact of Construction Project Complexity on Performance: an Empirical Study from China's Construction Industry - Shuyu Wang, Tongyin Han, Xuning Chen (Forest Chemicals Review, 1970)
There are many reasons for poor project management performance, and underestimating complexity is considered one of the main reasons.  However, there are still debates on the impact of project complexity on performance, and there is a lack of similar empirical studies in China.  Contractors are the main actors concerned with project management performance and need to manage their perceived project complexity.  Firstly, literature analysis method was used to determine the construction project complexity framework, a description model of social complexity, environmental complexity, technical complexity and stakeholder complexity was constructed, and 17 complexity factors were screened. Then questionnaire survey method was used to obtain data, 267 valid samples were collected from large-scale construction projects in China. Structural model path analysis shows that social complexity has a significant negative impact on performance, environmental complexity and stakeholder complexity have a negative but not significant impact on performance, and technological complexity has a positive impact on performance. Thus, different dimensions of complexity have different impacts on project management performance. Contractors should pay more attention to social complexity factors, strengthen communication with investors and local governments, concern on material supply chain risks and contract risks.